Splice variants of activation induced deaminase (AID) do not affect the efficiency of class switch recombination in murine CH12F3 cells. - Cesare Sala; Giorgio Mattiuz; Silvia Pietrobono; Andrea Chicca; Silvestro G Conticello (PLoS ONE, 2015)
Activation Induced Deaminase (AID) triggers the antigen-driven antibody diversification processes through its ability to edit DNA. AID dependent DNA damage is also the cause of genetic alterations often found in mature B cell tumors. A number of splice variants of AID have been identified, for which a role in the modulation of its activity has been hypothesized. We have thus tested two of these splice variants, which we find catalytically inactive, for their ability to modulate the activity of endogenous AID in CH12F3 cells, a murine lymphoma cell line in which Class Switch Recombination (CSR) can be induced. In contrast to full-length AID, neither these splice variants or a catalytically impaired AID mutant affect the efficiency of Class Switch Recombination. Thus, while a role for these splice variants at the RNA level remains possible, it is unlikely that they exert any regulatory effect on the function of AID.